Characterization of first and higher order statistics of mesoscales and sub-mesoscales in the MLT using Physics-informed machine learning - (:unkn) unknown (My University, 2026)
The mesosphere and lower thermosphere (MLT) represent a dynamically complex region governed by multiscale, nonlinear processes, including interactions between gravity waves and turbulence. Observing these dynamics at sufficient resolution is challenging d